Trips (Thysanoptera: Thripidae) yang berasosiasi dengan tanaman hortikultura di Jawa Barat dan kunci identifikasi jenis - Vani Nur Oktaviany Subagyo; Purnama Hidayat; Aunu Rauf; Dewi Sartiami (Perhimpunan Entomologi Indonesia, 2015)
Most of thrips from Thripidae family are pests on horticultural crops. To date, there are no records in the species richness of thrips in horticultural crops. The aim of the research is to conduct inventory on thrips spp diversity that are associated with horticultural crops in West Java. Sampling were done in several horticultural crops areas in Bogor, Cianjur, and Lembang (West Bandung). The identification process began with sample slide preparations along with the documentation of the character from each species. The identification was done mainly by using the identification program Oztrips and some other published identification keys. Identification key was built based on diagnosis characters of each species. The results found there were 15 species, that are Ceratothripoides brunneus, C. revelatus, Frankliniella intonsa, Megalurothrips typicus, M. usitatus, Scirtothrips dorsalis, Thrips aspinus, T. coloratus, T. hawaiiensis, T. javanicus, T. malloti, T. palmi, T. parvispinus, T. sumatrensis, and T. unispinus. T. aspinus and C. revelatus were new record for Indonesia.